Operator Theory in Krein Spaces and Nonlinear Eigenvalue Problems - Förster, Karl-Heinz; Jonas, Peter; Langer, Heinz (Operator Theory: Advances and Applications, 2006)
This volume contains 16 original research papers written by participants of the 3rd Workshop on Operator Theory in Krein Spaces and Nonlinear Eigenvalue Problems, which was held at the Technische Universität Berlin, Germany, December 12-14, 2003. They deal with spectral and perturbation theory of linear operators in indefinite inner product spaces and their applications. The topics include extension theory of symmetric operators, normal operators, realization theory and models of generalized Nevanlinna functions, interpolation problems, reproducing kernel spaces, matrix and operator pencils, locally definitizable functions, and semigroups.